Would Nonconsensual Criminal Neurorehabilitation Express a More Degrading Attitude Towards Offenders Than Consensual Criminal Neurorehabilitation? - Varelius Jukka (Springer, 2025)
It has been proposed that reoffending could be reduced by manipulating the neural underpinnings of offenders’ criminogenic mental features with what have been called neurocorrectives. The legitimacy of such use of neurotechnology – criminal neurorehabilitation, as the use is called – is usually seen to presuppose valid consent by the offenders subjected to it. According to a central criticism of nonconsensual criminal neurorehabilitation, nonconsensual use of neurocorrectives would express a degrading attitude towards offenders. In this article, I consider this criticism of nonconsensual criminal neurorehabilitation. By using cases of autonomous persons who lead a subservient existence as an example, I propose that nonconsensual criminal neurorehabilitation need not express a more degrading attitude towards offenders than consensual criminal neurorehabilitation. The argument of this article does not show that nonconsensual criminal neurorehabilitation is morally or legally acceptable. Yet, in view of the argument, criticizing nonconsensual criminal neurorehabilitation for expressing a degrading attitude towards offenders is not compatible with simultaneously endorsing consensual criminal neurorehabilitation.